Mortar plumpness detector and mortar plumpness detection method - Song Lijun; Gao Fuqiang; Yao Leibo; Wang Xiaoqiang (2016)
The invention relates to a mortar plumpness detector, comprising a panel; a plurality of contact switches are evenly arranged on one side of the panel, and a plurality of light-emitting diode (LED) lamps used for displaying whether the contact switches are in contact with mortar or not are arranged on the other side of the panel; each LED lamp corresponds to one contact switch; the panel is internally provided with a control circuit which is used for detecting whether the contact switches are in contact with the mortar or not and controlling on and off of the LED lamps corresponding to the contact switches; the control circuit is respectively connected with all the contact switches and LED lamps. The invention also provides a mortar plumpness detection method; the method comprises the steps of taking one panel, wherein the shape of the panel is the same as that of a to-be-detected surface of a brick, evenly arranging the contact switches on one side of the panel in m lines and n rows, and arranging the plural